Percutaneous afferent lymphatic vessel sclerotherapy for postoperative lymphatic leakage after previous ineffective therapeutic transpedal lymphangiography - Pan, Feng; Loos, Martin; Do, Thuy; Richter, Götz Martin; Kauczor, Hans-Ulrich; Hackert, Thilo; Sommer, Christof-Matthias (European radiology experimental, 2020)
To demonstrate the efficacy of percutaneous computed tomography (CT)-guided afferent lymphatic vessel sclerotherapy (ALVS) in the treatment of postoperative lymphatic leakage (LL) after ineffective therapeutic transpedal lymphangiography (TL).
Gesehen am 31.08.2021